(untitled) (Al-Qamar, 2022)
In the Islamic jurisprudence, law of inheritance has been deduced by Quran and Sunnah. This system of divine division of the inheritance of diseased person to his progeny in usūl and furū’ has an amazing philosophy behind it. The key feature of this law is the imperative determination of shares. After having gone through the injunctions regarding inheritance, an equilibrium and justified shape of share distribution appears without any exploitation. However, in this law, some impediments have also been described like denunciation of religion, apostasy, murder and slavery etc. In this article, we have discussed the reasons of deprivation of inheritance (impediments) according the opinions of Islamic jurisprudential experts while exploring the causes of their divergences in determining the impediments. As an ample of variant stand points among the Muslim scholar are reported and occurred about fixing the number and reasons of “mawāni’ al-irth”. For this purpose, fundamental sources have been applied and an effort has also been rendered to highlight the preferred standing.